SECURITY ISSUES AND RESOURCE PLANNING IN CLOUD COMPUTING (International Journal of Engineering and Computer Science, 2014)
With the rapid development of Internet, Cloud Computing has a vast area of the application such as security services, enhance efficiency of system by utilizing resources in cost effective manner. Cloud computing is simply a service that is sold and delivered on demand over the internet. Firstly, models of cloud computing discussed in this paper are: Service Model and Deployment model. Well-known service providers and vendors for these services of cloud computing are investigated. Secondly, the cloudlet relationship architecture and the resources management for them are described. Latter the security and privacy issues of cloud computing are discussed. Finally, the paper will be concluded on the benefits and applications of cloud com